High-conductivity manganese iron phosphate precursor, lithium manganese iron phosphate and preparation method
The introduction of nano-silica and glucose-modified carbon nanotubes into the lithium manganese iron phosphate precursor formation process addresses conductivity issues, creating a three-dimensional conductive network that enhances ion and electron mobility, thereby improving the material's performance.
Patent Information
- Application Number
- CN202411684651.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-03
AI Technical Summary
Lithium manganese iron phosphate batteries suffer from poor electronic conductivity due to the absence of a continuous FeO6 (MnO6) octahedral network and the presence of PO4 tetrahedrons, which limit lithium ion diffusion, and the addition of manganese further decreases conductivity.
A method involving the preparation of a high-conductivity ferromanganese phosphate precursor by introducing nano-silica into a nitric acid solution with specific manganese, iron, and phosphorus sources, followed by hydrofluoric acid treatment, and combining it with glucose-modified carbon nanotubes to form a three-dimensional conductive network.
The method enhances lithium ion and electron conductivity, providing a diffusion channel and improving the specific capacity and rate performance of the lithium manganese iron phosphate material.
Smart Images

Figure CN119240650A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a high-conductivity manganese iron phosphate precursor, lithium manganese iron phosphate and a preparation method thereof. Background Art
[0002] Lithium manganese iron phosphate (LMFP) with olivine structure is a type of phosphate system lithium-ion battery positive electrode material, mainly used in various lithium-ion batteries. LMFP batteries have many advantages such as safety, environmental protection, high cycle performance, low price, non-toxicity, and no environmental pollution. Compared with traditional lead-acid batteries, as well as new fuel cells, nickel-hydrogen batteries, and lithium manganese oxide batteries, the advantages are obvious. LMFP has the advantages of lithium iron phosphate and lithium manganese phosphate, with the same theoretical capacity of 170mAh / g, as well as higher safety and stability. At the same time, it has a higher operating voltage, which can reach about 4.1V, which is much higher than the 3.4V of lithium iron phosphate, so it has the potential advantage of high energy density. When the actual capacity of LMFP is used to the same extent as lithium iron phosphate, its energy density is 15-20% higher than that of lithium iron phosphate, and the upper limit of the driving range is further broken. LMFP is regarded as an upgraded version of lithium iron phosphate. It is a new type of positive electrode material obtained by adding manganese element to lithium iron phosphate. The best material performance is obtained by adjusting the Fe-Mn ratio. At the same time, it has a higher voltage platform, higher energy density and longer cycle life. It is becoming more and more popular in the power battery market.
[0003] However, although the olivine structure of LMFP improves the safety of the material, its electronic conductivity is poor. There is no continuous FeO6 (MnO6) octahedral network in the olivine structure, but it is connected by PO4 tetrahedrons, which limits the transfer of electrons and the insertion and deintercalation of lithium ions. In addition, the presence of PO4 tetrahedrons blocks the diffusion channel of lithium ions, so that lithium ions can only move in one-dimensional channels, resulting in a low diffusion rate of lithium ions. In addition, the addition of manganese also has a negative impact on conductivity. With the increase of manganese content, the conductivity and lithium ion conductivity of the material decrease at the same time. This is mainly because the presence of manganese makes it more difficult for lithium ions to be deintercalated and moved, resulting in poor conductivity. In addition, the different ratios of manganese to iron will affect the electrochemical properties of the material. Too much iron will lead to too low energy density, while too little iron will lead to poor electronic conductivity and low ion mobility. Summary of the invention
[0004] The object of the present invention is to provide a high-conductivity manganese iron phosphate precursor, lithium manganese iron phosphate and a preparation method to solve the problem of poor conductivity of lithium manganese iron phosphate batteries.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a high conductivity ferromanganese phosphate precursor, comprising the following steps:
[0007] S1. Add a manganese source, an iron source and a phosphorus source to a nitric acid solution, and then add nano-silica, and react at a constant temperature of 80-120°C for 4-6h under stirring conditions, filter, centrifuge, wash, dry, and collect the intermediate;
[0008] S2. Add the intermediate into HF solution to fully soak, filter and wash to obtain manganese iron phosphate precursor.
[0009] In a further embodiment of the present invention, the mass concentration of the nitric acid solution in S1 is 8-15%.
[0010] In a further embodiment of the present invention, the molar ratio of the manganese source, the iron source and the phosphorus source in S1 is 0.5-0.7:0.3-0.5:1-1.06.
[0011] In a further embodiment of the present invention, the manganese source and the iron source in S1 are any one of chloride, nitrate and ferric sulfate corresponding to manganese and iron respectively; the phosphorus source is any one of phosphoric acid and diammonium phosphate; preferably, the manganese source is manganese chloride, the iron source is ferric chloride, and the phosphorus source is phosphoric acid.
[0012] In a further embodiment of the present invention, the amount of nano-silicon dioxide in S1 is 1-3% of the total amount of the manganese source, the iron source and the phosphorus source.
[0013] In a further embodiment of the present invention, the mass concentration of the HF solution in S2 is 0.02-0.08%.
[0014] In a second aspect, the present invention provides a high-conductivity ferromanganese phosphate precursor, which is prepared according to the preparation method of the ferromanganese phosphate precursor described in the present invention.
[0015] In a third aspect, the present invention provides a method for preparing high-conductivity lithium manganese iron phosphate, which uses the above-mentioned lithium manganese iron phosphate precursor and specifically comprises the following steps:
[0016] Step 1: Preparation of glucose-containing carbon nanotubes:
[0017] At room temperature (25-30° C.), dichloromethane (DCM) was added to the carboxylated multi-walled carbon nanotubes, and after being mixed evenly, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and 4-dimethylaminopyridine (DMAP) were added to activate for 0.5-1 h, and then glucose was added, and the mixture was allowed to react for 10-12 h, and then the mixture was collected by centrifugation, washed, and dried to obtain glucose-containing carbon nanotubes;
[0018] Step 2: Preparation of lithium manganese iron phosphate:
[0019] A lithium source and glucose-containing carbon nanotubes are added to a manganese iron phosphate precursor, and after mixing, anhydrous ethanol is added according to a solid content of 50%, and the mixture is ball-milled for 8-12 hours and dried at 90-120° C. After being taken out and ground evenly, the mixture is placed in a nitrogen flow and calcined at 630-680° C. to obtain high-conductivity lithium manganese iron phosphate.
[0020] In a further embodiment of the present invention, the molar ratio of the ferromanganese phosphate precursor to the lithium source is 1:1-1.05.
[0021] In a further embodiment of the present invention, the amount of the glucose-containing carbon nanotubes is 6-10% of the total amount of the manganese iron precursor and the lithium source.
[0022] In a further embodiment of the present invention, the lithium source is Li2CO3.
[0023] In a further embodiment of the present invention, the usage ratio of the carboxylated multi-walled carbon nanotubes, DCM, EDC, DMAP and glucose is 1 g: 35 mL: 30 g: 10 g: 40-45 g.
[0024] In a fourth aspect, the present invention provides a high-conductivity lithium manganese iron phosphate, which is prepared according to any one of the above-mentioned methods for preparing lithium manganese iron phosphate.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention provides a high-conductivity ferromanganese phosphate precursor and a preparation method thereof. The ferromanganese phosphate precursor prepared by introducing nano-silicon dioxide into the ferromanganese phosphate and then soaking it in hydrofluoric acid to react with the nano-silicon dioxide introduced into the structure has a large number of pore structures, which further increases the specific surface area of the ferromanganese phosphate precursor. When used as a positive electrode material for a lithium battery, a diffusion and migration channel is provided for lithium ions, the migration path is effectively shortened, and the resistance to migration and diffusion is reduced, thereby improving the conductivity of the lithium ferromanganese phosphate positive electrode material.
[0027] 2. The ferromanganese phosphate precursor with a porous structure is used to further prepare lithium ferromanganese phosphate positive electrode material. Glucose-modified carbon nanotubes are used. Glucose is used as a structure-directing agent and a certain amount of carbon source to improve the interfacial interaction between the carbon nanotubes and the ferromanganese phosphate precursor and the lithium source, thereby realizing the formation of a three-dimensional conductive network, which not only improves the conductivity of electrons and ions, but also enhances the specific capacity and rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below in conjunction with the accompanying drawings.
[0029] Figure 1It is a schematic diagram of the preparation process of a high-conductivity ferromanganese phosphate precursor and lithium ferromanganese phosphate of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] See also Figure 1 , a method for preparing a high conductivity ferromanganese phosphate precursor, comprising the following steps:
[0032] S1. A manganese source, an iron source and a phosphorus source are added to a nitric acid solution having a mass concentration of 8-15% in a molar ratio of 0.5-0.7:0.3-0.5:1-1.06, and then 1-3% of the total amount of nano-silicon dioxide is added to the manganese source, iron source and phosphorus source. The reaction is carried out at a constant temperature of 80-120°C for 4-6h under stirring at 200rpm, filtered, centrifuged, washed, dried, and the intermediate is collected;
[0033] S2. The intermediate is added into a HF solution with a mass concentration of 0.02-0.08% to fully soak, and then filtered and washed to obtain a ferromanganese phosphate precursor.
[0034] Within the optional range, the manganese source includes but is not limited to manganese chloride, the iron source includes but is not limited to ferric chloride, and the phosphorus source includes but is not limited to phosphoric acid.
[0035] See also Figure 1 A method for preparing high-conductivity lithium manganese iron phosphate, which uses the above-mentioned lithium manganese iron phosphate precursor, specifically comprises the following steps:
[0036] Step 1: Preparation of glucose-containing carbon nanotubes:
[0037] Carboxylated multi-walled carbon nanotubes, DCM, EDC, DMAP and glucose were weighed according to the usage ratio of 1 g: 35 mL: 30 g: 10 g: 40-45 g;
[0038] Under room temperature, DCM is added to the carboxylated multi-walled carbon nanotubes, and after being mixed evenly, EDC and DMAP are added to activate for 0.5-1h, and then glucose is added, and the mixture is allowed to react for 10-12h, and the mixture is collected by centrifugation, washed and dried to obtain glucose-containing carbon nanotubes;
[0039] Step 2: Preparation of lithium manganese iron phosphate:
[0040] Weigh the ferromanganese phosphate precursor and Li2CO3 at a molar ratio of 1:1-1.05, and weigh the glucose-coated carbon nanotubes at 6-10% of the total amount of the ferromanganese phosphate precursor and the lithium source;
[0041] Add LiCO3 to the ferromanganese phosphate precursor, then add glucose-containing carbon nanotubes, add anhydrous ethanol according to 50% solid content after mixing, ball mill for 8-12 hours, and dry at 90-120°C; take out and grind evenly, place in a nitrogen flow, and calcine at 630-680°C to obtain high-conductivity lithium ferromanganese phosphate.
[0042] Example 1
[0043] See also Figure 1 , a method for preparing a high conductivity ferromanganese phosphate precursor, comprising the following steps:
[0044] S1. Manganese chloride, ferric chloride and phosphoric acid were added to a 12% nitric acid solution in a molar ratio of 0.6:0.4:1.04, and then 2% of nano-silicon dioxide was added to the total amount of manganese chloride, ferric chloride and phosphoric acid. The reaction was carried out at a constant temperature of 100 ° C for 5 h under stirring at 200 rpm, filtered, centrifuged, washed and dried to collect the intermediate;
[0045] S2. The intermediate is added into a HF solution with a mass concentration of 0.05% and fully immersed, and then filtered and washed to obtain a ferromanganese phosphate precursor.
[0046] Example 2
[0047] See also Figure 1 A method for preparing high-conductivity lithium manganese iron phosphate, which uses the manganese iron phosphate precursor prepared in Example 1, specifically comprising the following steps:
[0048] Step 1: Preparation of glucose-containing carbon nanotubes:
[0049] Carboxylated multi-walled carbon nanotubes, DCM, EDC, DMAP and glucose were weighed according to the usage ratio of 1 g: 35 mL: 30 g: 10 g: 42 g;
[0050] Under room temperature, DCM was added to the carboxylated multi-walled carbon nanotubes, and after being mixed evenly, EDC and DMAP were added to activate for 1 hour, and then glucose was added, and the mixture was allowed to react for 12 hours, and then the glucose-containing carbon nanotubes were obtained by centrifugation, washing and drying.
[0051] Step 2: Preparation of lithium manganese iron phosphate:
[0052] The ferromanganese phosphate precursor and Li2CO3 were weighed at a molar ratio of 1:1.05, and the glucose-containing carbon nanotubes were weighed at 8% of the total amount of the ferromanganese phosphate precursor and the lithium source;
[0053] Li2CO3 was added to the manganese iron phosphate precursor, and then glucose-containing carbon nanotubes were added. After mixing, anhydrous ethanol was added according to a solid content of 50%. After ball milling for 10 hours, it was dried at 100°C. After taking out, it was ground evenly, placed in a nitrogen flow, and calcined at 650°C to obtain high-conductivity lithium manganese iron phosphate.
[0054] Comparative Example 1
[0055] A method for preparing a ferromanganese phosphate precursor comprises the following steps:
[0056] S1. Add manganese chloride, ferric chloride and phosphoric acid in a molar ratio of 0.6:0.4:1.04 to a nitric acid solution having a mass concentration of 12%, stir at 200 rpm, and perform a hydrothermal reaction at 100 ° C for 5 h, filter, centrifuge, wash, dry, and collect the intermediate;
[0057] S2. The intermediate is added into a HF solution with a mass concentration of 0.05% and fully immersed, and then filtered and washed to obtain a ferromanganese phosphate precursor.
[0058] Comparative Example 2
[0059] A method for preparing lithium manganese iron phosphate, the preparation method of which is different from that of Example 2 in that the manganese iron phosphate precursor prepared in Comparative Example 1 is used, and the remaining steps and parameters remain the same.
[0060] Comparative Example 3
[0061] A method for preparing lithium manganese iron phosphate, which uses the manganese iron phosphate precursor prepared in Example 1, specifically comprising the following steps:
[0062] The ferromanganese phosphate precursor and Li2CO3 were weighed at a molar ratio of 1:1.05, and glucose was weighed at 8% of the total amount of the ferromanganese phosphate precursor and the lithium source;
[0063] Li2CO3 and glucose were added to the manganese iron phosphate precursor, and then anhydrous ethanol was added according to 50% solid content after mixing. After ball milling for 10 hours, it was dried at 100°C. After taking out, it was ground evenly, placed in a nitrogen flow, and calcined at 650°C to obtain high-conductivity lithium manganese iron phosphate.
[0064] Comparative Example 4
[0065] A method for preparing lithium manganese iron phosphate, which uses the manganese iron phosphate precursor prepared in Example 1, specifically comprising the following steps:
[0066] The ferromanganese phosphate precursor and Li2CO3 were weighed at a molar ratio of 1:1.05, and the carbon nanotubes were weighed at 8% of the total amount of the ferromanganese phosphate precursor and the lithium source;
[0067] Li2CO3 was added to the manganese iron phosphate precursor, and then glucose-containing carbon nanotubes were added. After mixing, anhydrous ethanol was added according to a solid content of 50%. After ball milling for 10 hours, it was dried at 100°C. After taking out, it was ground evenly, placed in a nitrogen flow, and calcined at 650°C to obtain high-conductivity lithium manganese iron phosphate.
[0068] Performance Test:
[0069] The resistivity of the lithium iron manganese phosphate positive electrode materials prepared in Example 2 and Comparative Examples 2 to 4 was measured using a four-probe resistivity tester. The test results are shown in Table 1.
[0070] The pole pieces made of the lithium manganese iron phosphate positive electrode materials prepared in Example 2 and Comparative Examples 2-4 were assembled into a button battery. The test results of specific capacity and capacity retention rate after 100 cycles at 1C rate are shown in Table 1; the test results of specific capacity after 5 cycles at 0.2C rate and 5 cycles at 10C rate are shown in Table 1.
[0071] Table 1
[0072]
[0073]
[0074] It can be seen from the test results in Table 1 that by introducing nano-silica into ferromanganese phosphate, and then using hydrofluoric acid immersion to react with the nano-silica introduced in the structure, pores are formed in the ferromanganese phosphate precursor, providing a channel for the diffusion and migration of lithium ions; and then glucose-treated carbon nanotubes are used, using glucose as a structure-directing agent and a certain amount of carbon source to improve the interface interaction between the carbon nanotubes and the ferromanganese phosphate precursor and the lithium source, thereby realizing the formation of a three-dimensional conductive network, which synergistically improves the conductivity of electrons and ions with the pores, and also enhances the specific capacity and rate performance of the material.
[0075] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high conductivity ferromanganese phosphate precursor, characterized in that: The following steps are involved: S1. Add a manganese source, an iron source and a phosphorus source to a nitric acid solution, and then add nano-silica, and perform a hydrothermal reaction at a constant temperature of 80-120°C for 4-6h under stirring conditions, filter, centrifuge, wash, dry, and collect the intermediate; S2. The intermediate is added into HF solution for soaking, filtered and washed to obtain manganese iron phosphate precursor.
2. The method for preparing a high conductivity ferromanganese phosphate precursor according to claim 1, characterized in that: The mass concentration of the nitric acid solution in S1 is 8-15%; The mass concentration of the HF solution in S2 is 0.02-0.08%.
3. The method for preparing a high conductivity ferromanganese phosphate precursor according to claim 1, characterized in that: The molar ratio of manganese source, iron source and phosphorus source in S1 is 0.5-0.7:0.3-0.5:1-1.06; The amount of nano silicon dioxide in S1 is 1-3% of the total amount of manganese source, iron source and phosphorus source.
4. The method for preparing a high conductivity ferromanganese phosphate precursor according to claim 1, characterized in that: In S1, the manganese source and the iron source are any one of chloride, nitrate and ferric sulfate corresponding to manganese and iron respectively; the phosphorus source is any one of phosphoric acid and diammonium phosphate.
5. A high conductivity ferromanganese phosphate precursor, characterized in that: It is prepared according to the preparation method of the high conductivity ferromanganese phosphate precursor according to any one of claims 1-4.
6. A method for preparing high-conductivity lithium manganese iron phosphate, characterized in that: The high conductivity ferromanganese phosphate precursor according to claim 5 is used, specifically comprising the following steps: Step 1, under room temperature, add DCM to the carboxylated multi-walled carbon nanotubes, mix well, then add EDC and DMAP to activate for 0.5-1h, then add glucose, let it stand for 10-12h, collect by centrifugation, wash and dry to obtain glucose-containing carbon nanotubes; Step 2: Add lithium source and glucose-containing carbon nanotubes to the manganese iron phosphate precursor, add anhydrous ethanol according to 50% solid content after mixing, ball mill for 8-12 hours, and dry at 90-120° C.; take out and grind evenly, place in a nitrogen flow, and calcine at 630-680° C. to obtain high-conductivity lithium manganese iron phosphate.
7. The method for preparing high-conductivity lithium manganese iron phosphate according to claim 6, characterized in that: The molar ratio of the ferromanganese phosphate precursor to the lithium source is 1:1-1.05; The amount of glucose-containing carbon nanotubes used is 6-10% of the total amount of the acid manganese iron precursor and the lithium source.
8. The method for preparing high-conductivity lithium manganese iron phosphate according to claim 6, characterized in that: The usage ratio of carboxylated multi-walled carbon nanotubes, DCM, EDC, DMAP and glucose is 1 g:35 mL:30 g:10 g:40-45 g.
9. A high conductivity lithium manganese iron phosphate, characterized in that: It is prepared according to the preparation method of high conductivity lithium manganese iron phosphate according to any one of claims 6-8.
Citation Information
Cited By
Lithium manganese iron phosphate positive electrode material and preparation method thereof
CN120717438A
A lithium iron manganese phosphate positive electrode material and a preparation method thereof
CN120717438B
Preparation method and application of nano lithium manganese iron phosphate
CN121134744A